2011
DOI: 10.1001/archpediatrics.2010.279
|View full text |Cite
|
Sign up to set email alerts
|

Post–High School Service Use Among Young Adults With an Autism Spectrum Disorder

Abstract: Objectives: To produce nationally representative population estimates of rates of service use among young adults with an autism spectrum disorder during their first few years after leaving high school and to examine correlates of use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
209
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 285 publications
(229 citation statements)
references
References 20 publications
13
209
0
1
Order By: Relevance
“…A recent study found that young adults on the autism spectrum whose parents reported they could perform four activities of daily living independently very well were less likely to receive medical services for diagnosis or evaluation related to disability than those who could not. 62 Our study furthers that finding, highlighting that high educational attainment does not necessarily eliminate the existence of important barriers to quality healthcare. We did not collect data on how often or in what ways participants access the Internet, nor did we collect data from participants without access to the Internet.…”
Section: Discussionsupporting
confidence: 72%
“…A recent study found that young adults on the autism spectrum whose parents reported they could perform four activities of daily living independently very well were less likely to receive medical services for diagnosis or evaluation related to disability than those who could not. 62 Our study furthers that finding, highlighting that high educational attainment does not necessarily eliminate the existence of important barriers to quality healthcare. We did not collect data on how often or in what ways participants access the Internet, nor did we collect data from participants without access to the Internet.…”
Section: Discussionsupporting
confidence: 72%
“…In this study we have demonstrated an interactive pathway between mastery, perceived stress, perceived support and physical health. Our findings underscore the importance of providing actual support or respite interventions during periods of high stress (Shattuck, et al, 2011;Nankervis, Rosewarne, & Vassos, 2011) to improve the health of these families. The results also suggest that the mastery may be a key mechanism in shielding parents of children with DD from poor physical health through its influence on stress appraisals.…”
Section: Resultsmentioning
confidence: 57%
“…caregivers to older adults vs controls) on cortisol functioning was found to be mediated by quality of social support (Kim & Knight, 2008), with caregivers reporting lower social support. More importantly however, our findings underscores the importance of providing psychosocial interventions to improve the health of family caregivers (Martire & Schulz, 2007), especially when evidence has found that their social interactions decline over time (Ray & Street, 2006;Shattuck, Wagner, Narendorf, Sterzing, & Hensley, 2011), depriving them of the much needed support. Thus, it could be that the mismatch between the availability of social support and the perceived need for it could result in a lowered perception of social support availability in these parents, leading in turn to increases of blood pressure.…”
Section: Discussionmentioning
confidence: 71%